Internet-Based Smart Door Design of Things (IOT) with Visitor Access Controller Indoor - Nurmuhlisa; Fauzi, Achmad; Sembiring, Hermansyah (Yayasan Kita Menulis, 2024)
In the era of digital technology, the Internet of Things (IoT) has become an innovative solution in various sectors, including in access management and room security. This research aims to design and implement an IoT-based smart door system that is able to control visitor access using NodeMCU ESP8266 and send notifications through the Telegram application. The system uses PIR sensors to detect the presence of visitors and servo motors to operate the door automatically. When the number of visitors reaches the maximum set capacity, the system will automatically close the door and send a warning notification to the Telegram bot and activate the buzzer as a warning sign. Thus, this system not only improves the safety and comfort of visitors, but also helps prevent the spread of diseases by limiting the number of visitors according to a safe capacity. The test results show that this smart door system can function well in controlling visitor access and providing real-time notifications when the room capacity is exceeded. The implementation of this system is expected to be applied in various public places to improve security management and visitor capacity effectively.